Military Zones: A Remedy of Awakening Ankara from Urban Amnesia - Zelal Oztoprak; Nur Çağlar (Anuari d’Arquitectura i Societat)
The historical context of Ankara is relatively complex due to the breaking points in its history. First, Ankara became the showcase of the newly established Turkish Republic and a new city center designed in isolation with the old one to represent the modernity of the Republic. Second, with the 1980 coup and expansion of the military zones, the new city center expanded unplanned and unexpected. Last, after the coup attempt in 2016, the large military zones in the city center are decided to be relocated to the city’s peripheries. This study points out the importance of this recent decision on the historical landscape of Ankara and proposes that it could be a potential for repairing the urban memory of the city. According to these massive changes, Ankara lost many of her historical references and the continuity of the urban memory. In this context, this paper thoroughly discusses the remaking of military zones in the city center, their historical presence, and possible interactions with the city’s needs. Understanding these areas as potential catalysts for repairing the historical landscape requires developing a new perspective, which embraces complex relations and multiple voices. Dialogic and polyphonic thinking encompasses the city’s inherent multiplicity, relationality, incompleteness, and historical assets.